2004
DOI: 10.1038/nature02593
|View full text |Cite
|
Sign up to set email alerts
|

Global biodiversity patterns of marine phytoplankton and zooplankton

Abstract: Although the oceans cover 70% of the Earth's surface, our knowledge of biodiversity patterns in marine phytoplankton and zooplankton is very limited compared to that of the biodiversity of plants and herbivores in the terrestrial world. Here, we present biodiversity data for marine plankton assemblages from different areas of the world ocean. Similar to terrestrial vegetation, marine phytoplankton diversity is a unimodal function of phytoplankton biomass, with maximum diversity at intermediate levels of phytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
283
4
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 388 publications
(330 citation statements)
references
References 26 publications
41
283
4
2
Order By: Relevance
“…We found that the maximum group-specific Chl a concentrations for prasinophytes, haptophytes, phototrophic dinoflagellates and to some extent pelagophytes (summer) coincided with the shallowing of the nutricline. The association of phototrophic dinoflagellates and pelagophytes with higher nutrient concentrations is not surprising considering their relatively large cell size (Irigoien et al 2004;Edwards et al 2012). Dinoflagellates, however, were most prevalent during the summer in the north, which agrees with their tendency to favor warmer waters, with shallower Z m , higher mean irradiance and reduced vertical mixing (Irwin et al 2012).…”
Section: Component Sourcesupporting
confidence: 64%
“…We found that the maximum group-specific Chl a concentrations for prasinophytes, haptophytes, phototrophic dinoflagellates and to some extent pelagophytes (summer) coincided with the shallowing of the nutricline. The association of phototrophic dinoflagellates and pelagophytes with higher nutrient concentrations is not surprising considering their relatively large cell size (Irigoien et al 2004;Edwards et al 2012). Dinoflagellates, however, were most prevalent during the summer in the north, which agrees with their tendency to favor warmer waters, with shallower Z m , higher mean irradiance and reduced vertical mixing (Irwin et al 2012).…”
Section: Component Sourcesupporting
confidence: 64%
“…9). The range in modeled SI compares to that reported by Irigoien et al (2004) but not to the high cytometric diversity values of Li (2002), which upon conversion of the exponential form reach high diversity values of 4.3 due to the representation of both physiological and genetic variation among organisms rather than solely taxonomy. Similar to the observed scatter reported by most observations in non-marine (Adler et al, 2011) and marine (Li, 2002;Irigoien et al, 2004;Duarte et al, 2006) systems, the scatter in our model results does not reveal a straightforward curvilinear relationship between diversity and productivity, consistent with Adler et al's (2011) argument that many factors contribute to the variation in diversity and therefore diversity-productivity relationships.…”
Section: The Diversity-productivity Scattermentioning
confidence: 54%
“…6 suggests a triangular (SR) or irregular (SI) shape; the lower bound argues for a flat relationship. Qualitatively, this scatter of points fill in areas whose shapes resemble that formed by the distribution of points obtained in the comprehensive studies of marine phytoplankton by Li (2002) and Irigoien et al (2004) (Fig. 9).…”
Section: The Diversity-productivity Scattermentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions are typical of intermittent nutrient pulses that allow phytoplankton bloom dominated by a few high-fitness species to occur in temperate ocean [Margalef, 1978;Li, 2002;Irigoien et al, 2004]. Indeed, the reduced mixing and reduced mixed-layer depth are more beneficial to large phytoplankton, mainly fast-growing diatoms, that are less efficient at low light levels than smaller cells.…”
Section: 1002/2017gl074173mentioning
confidence: 99%